The USE OF PROJECT-BASED LEARNING IN TEACHING CCU (CROSS CULTURAL UNDERSTANDING) AT THE SIXTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF PURWOREJO MUHAMMADIYAH UNIVERSITY: A CLASSROOM OBSERVATION - Titi Rokhayati (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
Project-based learning (PBL) is very important for the students since in this project students learn many things. They learn how to have a survey, collecting data, cooperate with friends, find the respondent, present the data and conclude all things in the project. CCU or Cross-Cultural Understanding is one of the subjects which is compulsory for English Department students. The PBL is appropriate to be applied in CCU since at the end of the semester the students have to research on Culture by having the respondents in the surroundings. This research is a classroom observation research in which semester six are the samples. The finding said that collaboration, asking questions, reflecting and, presenting are some aspect which 100% happened in the classroom while the result of students’ questionnaire said that the students enjoy the class and they can take much benefit from the class.